STRESS INOCULATION TRAINING DALAM MENINGKATKAN KESEHATAN MENTAL REMAJA - M.Elyas Arif Budiman; Zidni Nuris Yuhbaba; Wahyi Sholehah Erdah Suswati (Jurnal SADEWA, 2025)
The problem of adolescent mental health around the world continues to grow and has a lifelong impact on individuals and society. This global challenge is multidimensional which certainly requires a comprehensive approach, many interventions continue to seek solutions that only address problems in adolescents. The purpose of the Community Service Activity is mental health through stress inoculation training interventions. The intervention given to 50 adolescents is stress inoculation training consisting of 8 sessions, namely: topic explanation, relaxation education, cognitive concept habituation, negative thought test challenges, self-talk education, distraction concentration technique education, problem solving education and the last session is communication skills. The results of this activity showed that the results before the intervention showed that 64% of adolescents experienced mental disorders and after the intervention activity there was an increase, namely adolescents had good mental health as much as 76%. Stress inoculation training will provide a guidance process for various interventions that can be applied independently by adolescents and explored together.